2018
DOI: 10.1002/chem.201800895
|View full text |Cite
|
Sign up to set email alerts
|

Regioisomeric Tandem Triblock Shape Amphiphiles Based on Polyhedral Oligomeric Silsesquioxanes

Abstract: We report the design, synthesis and self-assembly of a series of tandem triblock shape amphiphile regioisomers composed of one rod-like fluorinated polyhedral oligomeric silsesquioxane (FPOSS) cage tethered with two spherical tert-butyl-POSS (tBPOSS) cages in para-, meta-, and ortho-configurations. Precision syntheses are achieved through sequential "click" reactions and the compounds are thoroughly characterized by combined techniques of NMR, FT-IR and MALDI-TOF MS spectroscopy. Only the ortho-isomer forms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
(29 reference statements)
0
10
1
Order By: Relevance
“…Bulk crystallization prevents the formation of such single crystals, and thus, they are not further investigated. Our previous studies on double-chain giant surfactants (DPOSS-2PS n ) showed the opposite order of phase stability with the ortho -isomer being the most stable one in most cases ( ortho- > meta- > para- ), ,, which may seem contradictory to the current result at first glance. However, a second thought would clarify that the underlying principles are similar.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Bulk crystallization prevents the formation of such single crystals, and thus, they are not further investigated. Our previous studies on double-chain giant surfactants (DPOSS-2PS n ) showed the opposite order of phase stability with the ortho -isomer being the most stable one in most cases ( ortho- > meta- > para- ), ,, which may seem contradictory to the current result at first glance. However, a second thought would clarify that the underlying principles are similar.…”
Section: Resultscontrasting
confidence: 99%
“…This “molecular Lego” approach is powerful in preparing monodisperse giant molecules with high molecular weight and controlled sequences and topology. Among these molecules, POSS compounds stand out due to their high molecular symmetry and multiple vertices that can be easily functionalized. Based on the T 8 -POSS scaffold, many Janus derivatives have been prepared, such as monoadducts, regioisomeric diadducts and triadducts, , and even the tetra-adduct regioisomers. , We have previously achieved the successful separation of different regioisomers in moderate yields which facilitates the study of their structure–property relationships. , It has been shown that the regioconfiguration does exert a profound influence on the self-assembly of regioisomeric giant surfactants and shape amphiphiles, causing systematic changes in phase structure and phase stability. It remains to be demonstrated if such effects are general to other giant molecules, such as the molecular Janus particles. ,, …”
Section: Introductionmentioning
confidence: 99%
“…It was speculated that, unlike coil‐like PS, the rigid BPOSS could hardly deform to compensate for the unfavorable configuration for packing in the meta ‐isomer. The use of non‐crystalline tert‐butyl ‐functionalized POSS ( t BPOSS) and crystalline rod‐like fluoroalkyl‐functionalized POSS (FPOSS) gives a different set of anisotropic shape amphiphiles, FPOSS‐2 t BPOSS . In this case, only the ortho ‐isomer could form ordered lamellar structures, the other two isomers are amorphous (Figure b).…”
Section: Regio‐isomersmentioning
confidence: 99%
“…Adding a third block to the shape amphiphile would be anticipated to generate even more complexity and diversity [26]. For example, tandem triblock shape amphiphilic regio-isomers based on POSS were found to exhibit distinct self-assembling behaviors [27]. If the third block is of distinct shape, the situation would be even more interesting.…”
Section: Introductionmentioning
confidence: 99%